Autophagy and its therapeutic potential in diabetic nephropathy - Han, Yu-Peng; Liu, Li-Juan; Yan, Jia-Lin; Chen, Meng-Yuan; Meng, Xiang-Fei; Zhou, Xin-Ru; Qian, Ling-Bo (Frontiers in Endocrinology, 2023)
Diabetic nephropathy (DN), the leading cause of end-stage renal disease, is the most significant microvascular complication of diabetes and poses a severe public health concern due to a lack of effective clinical treatments. Autophagy is a lysosomal process that degrades damaged proteins and organelles to preserve cellular homeostasis. Emerging studies have shown that disorder in autophagy results in the accumulation of damaged proteins and organelles in diabetic renal cells and promotes the development of DN. Autophagy is regulated by nutrient-sensing pathways including AMPK, mTOR, and Sirt1, and several intracellular stress signaling pathways such as oxidative stress and endoplasmic reticulum stress. An abnormal nutritional status and excess cellular stresses caused by diabetes-related metabolic disorders disturb the autophagic flux, leading to cellular dysfunction and DN. Here, we summarize the role of autophagy in DN focusing on signaling pathways to modulate autophagy and therapeutic interferences of autophagy in DN.